2014
DOI: 10.5194/angeo-32-121-2014
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-16-day periodic meridional movement of the equatorial ionization anomaly

Abstract: Abstract. Based on the daytime location of the equatorial ionization anomaly (EIA) crest derived from GPS observations at low latitude over China during the 2005-2006 stratospheric sudden warming (SSW), a quasi-16-day periodic meridional movement of EIA crest with the maximum amplitude of about 2 degrees relative to the average location of EIA crest has been revealed. In addition, periodic variations that are in phase with the meridional EIA movement are also revealed in the equatorial electrojet (EEJ) and F2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 42 publications
(73 reference statements)
6
20
0
Order By: Relevance
“…This 14‐ to 15‐day oscillation in China EIA region had been found in our prior studies, which were termed the quasi 16‐day period according to the naming rules of quasi 16‐day period in atmosphere. As confirmed by our previous research, this 14‐ to 15‐day periodic movement in EIA crest during this SSW event should not be of solar/magnetic activity origin (Mo et al, , ). Moreover, the amplitudes of 14‐ to 15‐day oscillations in China sector, in order of highest to lowest, are during 2009, 2006, and 2003 SSW period.…”
Section: Results and Analysissupporting
confidence: 82%
See 2 more Smart Citations
“…This 14‐ to 15‐day oscillation in China EIA region had been found in our prior studies, which were termed the quasi 16‐day period according to the naming rules of quasi 16‐day period in atmosphere. As confirmed by our previous research, this 14‐ to 15‐day periodic movement in EIA crest during this SSW event should not be of solar/magnetic activity origin (Mo et al, , ). Moreover, the amplitudes of 14‐ to 15‐day oscillations in China sector, in order of highest to lowest, are during 2009, 2006, and 2003 SSW period.…”
Section: Results and Analysissupporting
confidence: 82%
“…Second, the peaks of 14‐ to 15‐day waves in the location of EIA crest are always 4–6 days later than the dates of new moon or full moon. Further, 14‐ to 15‐day waves in the location of EIA crest are in‐phase with that in EEJ and h m F 2 (Figure ) (Mo et al, ), indicating that in the peaks of EEJ and h m F 2 , EIA crest locations happen 4–6 days after new moon or full moon. That consistent phase lag was relative to new moon or full moon had also been revealed in EEJ, plasma drifts, and TEC due to semidiurnal lunar wave effect (Fejer et al, ; Goncharenko et al, ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Earlier studies have demonstrated that the largest variations in VTEC during SSW are observed at the crests of the EIA [Goncharenko et al, 2010a;Liu et al, 2011], and the location of the crests can vary periodically by several degrees in latitude [Mo et al, 2014]. In addition, the difference from one station to another is related with superimposed perturbation caused by MSTID and/or PW disturbances.…”
Section: 1002/2014ja020649mentioning
confidence: 98%
“…The most commonly observed planetary waves to which atmosphere readily responds are those having periodicities 2, 5, 10, and 16 days (Salby, 1981;Williams & Avery, 1992). It has been shown that PWs significantly influence many of the processes over the equator (Anderson & Araujo-Pradere, 2010;Goncharenko et al, 2010;Mo et al, 2014) including the PSSR and the occurrence of ESF (Abdu et al, 2006;Bertoni et al, 2010). In fact, Abdu et al (2006) have reported episodes of PW oscillations in the evening time vertical drift/zonal electric field (prereversal enhancement, PRE) over the equatorial F region, with periods ranging from~2 to~7 days concurrently with its presence in the mesospheric winds.…”
Section: Introductionmentioning
confidence: 99%